2016
DOI: 10.1016/j.bbi.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of brain T cells in homeostatic conditions in lymphopenic Rag2−/− mice

Abstract: The concept of the brain as an immune privileged organ is rapidly evolving in light of new findings outlining the sophisticated relationship between the central nervous and the immune systems. The role of T cells in brain development and function, as well as modulation of behavior has been demonstrated by an increasing number of studies. Moreover, recent studies have redefined the existence of a brain lymphatic system and the presence of T cells in specific brain structures, such as the meninges and choroid pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
5
35
0
Order By: Relevance
“…A vivid in vivo demonstration of T cell residence in the brain following adoptive transfer of green fluorescent protein (GFP)-positive lymph node cells in Rag2 −/− mice was recently published (Song et al, 2016). As expected, several weeks after repopulation into a naïve mouse, fluorescent lymphocytes were found scattered within the meninges, choroid plexus, and the circumventricular organs.…”
Section: Mechanisms Of Immune-to-brain Influencementioning
confidence: 99%
See 1 more Smart Citation
“…A vivid in vivo demonstration of T cell residence in the brain following adoptive transfer of green fluorescent protein (GFP)-positive lymph node cells in Rag2 −/− mice was recently published (Song et al, 2016). As expected, several weeks after repopulation into a naïve mouse, fluorescent lymphocytes were found scattered within the meninges, choroid plexus, and the circumventricular organs.…”
Section: Mechanisms Of Immune-to-brain Influencementioning
confidence: 99%
“…As expected, several weeks after repopulation into a naïve mouse, fluorescent lymphocytes were found scattered within the meninges, choroid plexus, and the circumventricular organs. Labeled cells within brain parenchyma were scarce and were largely confined to perivascular spaces (Song et al, 2016). Importantly, lymphocytes were not reported in the hippocampal vascular niche that supports DG neurogenesis (Palmer et al, 2000) in this or any other study to date.…”
Section: Mechanisms Of Immune-to-brain Influencementioning
confidence: 99%
“…Expression of this cytokine in the brain has been shown in varied cell types, but more prominently in microglial and perivascular cells [38]. Recently, lymphocytes and T cells have been shown to circulate in a brain lymphatic system [39], and work from our group has shown that they proliferate in the brain of reconstituted Rag2 −/− mice with a significant degree of interaction with the microvasculature during this process [32]. Thus, it is possible that CD8 + T cells increase their interaction with the brain microvasculature in response to stress, stimulating the production of IL-1β by perivascular cells, similar to the model of stress-induced vascular inflammation in hypertension [28].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenic Rag2 −/− mice were reconstituted by adoptive transfer with 8–10 million naive CD4 + (n = 23) or CD8 + (n = 21) T cells in a 1:1 donor to recipient transfer from age-matched WT mice. Donor cells were prepared as previously described [32] using the EasySep CD4 + or CD8 + purification kits (Stem Cell Technologies, Vancouver, BC, Canada) following manufacturer’s guidelines. Control Rag2 −/− mice (n = 18) received PBS only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation